My OS ought to know me better: In-app behavioural analytics as an OS service - Fernandes, Earlence; Riva, Oriana; Nath, Suman (Workshop on Hot Topics in Operating Systems (HotOS), 2015)
What a user does in an app (e.g., viewing the menu of a restaurant or listening to the same song several times) is key to understanding user interests and preferences, and ultimately to enabling personalized experiences. This kind of behavioural analytics information, as we call it, is rarely used today (and if it is used, it remains siloed in one app). This paper makes a case for the OS to provide an in-app behavioural analytics service which monitors user activities within an app to extract such analytics and to share them with other apps in a secure, private and uniform way. All this must be achieved with zero developer effort and with low resource overhead.